Hubungan Kongruensi Karir Remaja-Orang Tua dengan Integritas Akademik - Kholifah Umi Sholihah; Badik Atul Alieffah; Aula Fata Nabila (Syntax Idea)
Integrity Academic integrity is the behavior of a person to be honest and fair in academic activities. Academic integrity is something that must be owned because it also has an impact on one's attitude when entering the world of work. The research conducted focuses on knowing the relationship between adolescent-parent career congruence and academic integrity. This research is a quantitative involving 140 students. The sampling technique used was convenience sampling. The measuring instrument used has adequate reliability with a Cronbach's Alpha (Î±) value: 0,889-0,956. Data analysis was conducted using spearman rank analysis with the help of the SPSS 25 application. The results of the research conducted showed that adolescent-parent career congruence has a significant relationship with academic integrity. The relationship between the two variables is characterized by a significance value of 0.004 (p < 0.05) with a correlation value of 0.243. There is a relationship between the two variables, so to support the academic integrity of students, parents need to be positively involved in the process of determining their children's careers, one of which is by having alignment between the expected career and the career desired by the child